Non-cardiac benefits of human recombinant erythropoietin in end stage renal failure and anaemia. Issue 5 (November 1993) - Morris, K P; Sharp, J; Watson, S; Coulthard, M G
Abstract : Recombinant human erythropoietin (r-HuEpo) is now available to correct the anaemia of end stage renal failure. The clinical consequences of increasing the haemoglobin concentration in children on dialysis are incompletely documented; a placebo controlled study is essential when assessing subjective changes, for example in appetite or other aspects of quality of life. A single blind, placebo controlled crossover study in 11 children with end stage renal failure was performed to assess the clinical benefits resulting from correction of anaemia. Ten of the 11 children completed 36 weeks of the study and seven completed both 24 week limbs. Subcutaneous administration of r-HuEpo twice a week resulted in an increase in haemoglobin concentration, from 73 to 112 g/l. This was associated with an objective improvement in exercise tolerance, and a subjective improvement in physical performance and health, and better school attendance. No consistent effect was seen on appetite, growth, psychosocial functioning, biochemical control, or peritoneal dialysis efficiency. A small but clinically unimportant increase in systolic and diastolic blood pressure was seen in five children. One child on antihypertensive treatment required an increase in dosage during r-HuEpo while another child required a reduction in treatment. These findings, together with the important cardiac benefits previously described during r-HuEpo treatment, support the use of r-HuEpo in all children with end stage renal failure and anaemia.